2011
DOI: 10.1073/pnas.1103216108
|View full text |Cite
|
Sign up to set email alerts
|

Direct visualization of myosin-binding protein C bridging myosin and actin filaments in intact muscle

Abstract: Myosin-binding protein C (MyBP-C) is a thick filament protein playing an essential role in muscle contraction, and MyBP-C mutations cause heart and skeletal muscle disease in millions worldwide. Despite its discovery 40 y ago, the mechanism of MyBP-C function remains unknown. In vitro studies suggest that MyBP-C could regulate contraction in a unique way—by bridging thick and thin filaments—but there has been no evidence for this in vivo. Here we use electron tomography of exceptionally well preserved muscle t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
231
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 171 publications
(254 citation statements)
references
References 46 publications
19
231
2
2
Order By: Relevance
“…On the basis of yeast 2 hybrid experiments, it was concluded that the C1 and M domains were necessary for actin binding and that replacement of endogenous cMyBP-C with actin binding-ablated cMyBP-C resulted in its abnormal sarcomeric distribution and disturbance of the sarcomeric structure (9). These in vitro demonstrations of actin binding are supported by electron tomographic observations showing MyBP-C extending from the thick to the thin filaments in the intact sarcomere, consistent with a model in which the N terminus of MyBP-C binds to the thin filament (21,22). Together, these results suggest that actin binding is physiologically relevant and that the slowing of actin filament sliding is one possible mechanism by which cMyBP-C modulates cardiac contractility (5,23,24).…”
supporting
confidence: 67%
See 1 more Smart Citation
“…On the basis of yeast 2 hybrid experiments, it was concluded that the C1 and M domains were necessary for actin binding and that replacement of endogenous cMyBP-C with actin binding-ablated cMyBP-C resulted in its abnormal sarcomeric distribution and disturbance of the sarcomeric structure (9). These in vitro demonstrations of actin binding are supported by electron tomographic observations showing MyBP-C extending from the thick to the thin filaments in the intact sarcomere, consistent with a model in which the N terminus of MyBP-C binds to the thin filament (21,22). Together, these results suggest that actin binding is physiologically relevant and that the slowing of actin filament sliding is one possible mechanism by which cMyBP-C modulates cardiac contractility (5,23,24).…”
supporting
confidence: 67%
“…In the intact sarcomere, MyBP-C is thought to bind by its 3 C-terminal domains to the thick filament backbone, whereas the rest of the molecule extends to adjacent thin filaments (5,22,51,52). Thus, although the molar ratio of MyBP-C to actin subunits in the C-zone is only ∼1:10, the proximity of its N termini to actin may make their effective local concentration high enough to bind the thin filament without substantial occupancy of S1 binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…The first-order myosin meridional reflection, M1, has the contribution of the MyBP-C, which is present in the C zone of the thick filament with an ∼43-nm periodicity (3,23). The second (M2), fourth (M4), and fifth orders (M5) are the so-called forbidden reflections associated with the perturbations of the helical symmetry of the myosin motors in the C-zone of the thick filament (24,25).…”
Section: Sl-tension Relationmentioning
confidence: 99%
“…1A) (4,5). The C-terminal domain (C10) is tightly bound to the thick filament backbone, and the N-terminal domains extend radially from the thick filament (6,7). Thus cMyBP-C's N-terminal domains are positioned to bind to neighboring actin filaments and/or the myosin S2 domain to modulate actomyosin activity.…”
mentioning
confidence: 99%